2023
DOI: 10.2147/ijn.s404848
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bond-Based SN38 Prodrug Nanoassemblies with High Drug Loading and Reduction-Triggered Drug Release for Pancreatic Cancer Therapy

Abstract: Purpose Chemotherapy is a significant and effective therapeutic strategy that is frequently utilized in the treatment of cancer. Small molecular prodrug-based nanoassemblies (SMPDNAs) combine the benefits of both prodrugs and nanomedicine into a single nanoassembly with high drug loading, increased stability, and improved biocompatibility. Methods In this study, a disulfide bond inserted 7-ethyl-10-hydroxycamptothecin (SN38) prodrug was rationally designed and then used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…For the preparation of nanobinders (NBs), several parameters must be thoughtfully considered, including their stability over time, the percentage of tEB functionalization to allow proper binding with HSA, and the Nlg/Ptx ratio, which should be in favor of Nlg ( Sonpavde et al, 2020 ). Moreover, it is established that homodimeric disulfide prodrugs, such as Nlg dimer, i.e., NlgD ( Figure 1 ; Supplementary Material ), ( Feng et al, 2018 ) can enhance the stability of prodrug-based nanoassemblies and facilitate the reduction-responsive release of active drugs ( Zhou et al, 2021 ; Liu et al, 2022 ; Zhong et al, 2023 ). Therefore, to achieve greater flexibility in the composition of NBs concerning stability and drug ratio, we chose to synthesize a monomeric HSA-binding analogue of Nlg, i.e., nMAC ( Scheme 3 ), to be combined with pMACs and NlgD (see § 3.4).…”
Section: Resultsmentioning
confidence: 99%
“…For the preparation of nanobinders (NBs), several parameters must be thoughtfully considered, including their stability over time, the percentage of tEB functionalization to allow proper binding with HSA, and the Nlg/Ptx ratio, which should be in favor of Nlg ( Sonpavde et al, 2020 ). Moreover, it is established that homodimeric disulfide prodrugs, such as Nlg dimer, i.e., NlgD ( Figure 1 ; Supplementary Material ), ( Feng et al, 2018 ) can enhance the stability of prodrug-based nanoassemblies and facilitate the reduction-responsive release of active drugs ( Zhou et al, 2021 ; Liu et al, 2022 ; Zhong et al, 2023 ). Therefore, to achieve greater flexibility in the composition of NBs concerning stability and drug ratio, we chose to synthesize a monomeric HSA-binding analogue of Nlg, i.e., nMAC ( Scheme 3 ), to be combined with pMACs and NlgD (see § 3.4).…”
Section: Resultsmentioning
confidence: 99%
“…pH-dependent degradation of ortho ester linkages in NP2 was determined using 1 H NMR. The in vitro release of DOX and 5FU from NPs/DOX was measured by a dialysis method . These detailed methods are described in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro release of DOX and 5FU from NPs/DOX was measured by a dialysis method. 26 These detailed methods are described in the Supporting Information.…”
Section: Preparation Of Nps and Dox-loaded Nps (Nps/dox)mentioning
confidence: 99%
“…In vivo experiments in 4T1 tumor-bearing model revealed that the tumor weight was significantly lower in the administration group mice than in the saline group, and the SN38-SS-PC liposome group had the lowest tumor weight with a tumor inhibition rate (TIR) of approximately 53.3%, which was significantly higher than that of irinotecan at 11.7%. Zhong et al 97 inserted disulfide bonds into SN38 and used it to prepare GSH responsive nanoassemblies (SNSS NAs). SNSS NAs were able to increase the absorption of Panc-2 and BxPC-3 cells when compared to free SN38, and in vitro cellular uptake demonstrated that SNSS NAs were internalized via a clathrin-mediated exocytosis pathway.…”
Section: Physio-chemical Targeted Drug Delivery Systemsmentioning
confidence: 99%